Analysis of Adjective Clauses in the Novel “The Little Prince” by Antonie De Saint Exupéry - Yuliani, Anisa Eka; Maghfiroh, Ana; Asiyah, Siti; Mustikawati, Diyah Atiek; Indriastuti, Niken Reti (Universitas Muhammadiyah Surakarta, 2022)
An adjective clause is a dependent clause that identifies or provides additional information about a noun. In this study, the researcher examines the use of adjective clauses in the novel The Little Prince by Antoine de Saint-Exupéry. The research aims to identify adjective clauses based on their types and functions. Additionally, the researcher investigates which adjective clauses are most frequently used in the novel. Consequently, the adjective clauses in the novel are easily identifiable and suitable for analysis. The research design is a qualitative study utilizing content analysis to identify adjective clauses in The Little Prince. The researcher identified 16 adjective clauses and categorized them according to their types and functions. Based on type, there are 12 restrictive clauses (75%) and 4 non-restrictive clauses (25%). In terms of function, 10 clauses are relative pronouns (62.5%) and 6 are relative adverbs (37.5%), with relative pronouns being more prevalent. For future research, the researcher recommends a more comprehensive approach and accurate findings to benefit further studies and contribute to educational advancement.